LIBERALISASI JASA DISTRIBUSI, MASUKNYA MODAL ASING DAN HUBUNGANNYA DENGAN MODAL DOMESTIK INDONESIA - Muhammad Fawaiq (EKUITAS (Jurnal Ekonomi dan Keuangan), 2018)
The aims of this study are to determine the level of liberalization of the services sector and to analyze a causal relationship between Foreign Direct Investment/FDI (as a result of the liberalization of the distribution service) and Domestic Investment/DI in the sector. The method used in this research are descriptive analysis and Panel-VECM-Granger. The results showed that the degree of liberalization of distribution services, especially related to FEP has not met the target of liberalization of MEA 2015. Hypothesis testing results show that there is a unidirectional Granger-Causality relationship in short-term and long-term between FDI and DI. That relationship is FDI strongly influencing DI in the Indonesian distribution services sector. ECT value of the independent variable of FDI is -1.0, which means that the speed of change in the value of DI that caused by the changes of FDI to achieve a equilibrium is 100 percent per year. Thus it is known that the entry of FDI encourage domestic investment activity in the Indonesian distribution services sector. The results of this study need to be considered in terms of improvement FEP in the distribution services sector. FEP improvement policy will encourage the entry of FDI and indirectly encourages DI.